Adaptive full-range decoupled ventilation strategy and air-conditioning systems for cleanrooms and buildings requiring strict humidity control and their performance evaluation. (1st February 2019) - Zhuang, Chaoqun; Wang, Shengwei; Shan, Kui
Abstract: The air-conditioning systems in buildings and spaces, such as cleanrooms, requiring strict space humidity control are usually energy intensive, where significant energy wastes often occur due to improper system design and control. Dedicated outdoor air ventilation strategy, as the most recommended solution today, offers good energy performance by fully decoupling the cooling and dehumidification process. But its energy saving potential is restricted to a range of working conditions, due to the excessive outdoor air intake, it cannot provide energy-efficient operation when the internal latent load and ambient enthalpy are high. This paper therefore proposes a novel "adaptive full-range decoupled ventilation strategy", which offers optimized energy-efficient operation by incorporating the advantages of different ventilation strategies and adopting an adaptive economizer. This study also addresses the design of the air-conditioning systems for the implementation of the proposed ventilation strategy. The energy performance and economic analysis of the air-conditioning systems adopting the proposed ventilation strategy are investigated and compared with most updated strategies available. Results show that the proposed ventilation strategy can offer superior energy performance over the full range of internal load and weather conditions while the initial cost is even lower than that for the most recommended ventilation strategy today. Highlights: A novel "adaptive full-range decoupled ventilation strategy" is proposed for cleanrooms. The strategy also incorporates a new "adaptive economizer" including three modes. The strategy offers superior energy performance over the full range of operation conditions. Significant energy saving can achieved using the proposed strategy. Initial cost for proposed strategy is medium and lower that for most popular strategy today.